2018
DOI: 10.1017/s0033291718001782
|View full text |Cite|
|
Sign up to set email alerts
|

A pre-post pilot study of electronic cigarettes to reduce smoking in people with severe mental illness

Abstract: The provision of e-cigarettes is a potentially useful harm reduction intervention in smokers with a psychotic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In the Smoking Toolkit Study, they were also associated with increased success rates for smokers with and without mental health problems [40]. Additionally, smaller studies in smokers with severe mental illness who were not interested in quitting found that substantial proportions reduced their smoking by at least 50% when supplied with e-cigarettes [42,43]. Clinicians should ensure that patients (both inpatient and community) have their smoking status identified and recorded in health care records.…”
Section: Discussionmentioning
confidence: 99%
“…In the Smoking Toolkit Study, they were also associated with increased success rates for smokers with and without mental health problems [40]. Additionally, smaller studies in smokers with severe mental illness who were not interested in quitting found that substantial proportions reduced their smoking by at least 50% when supplied with e-cigarettes [42,43]. Clinicians should ensure that patients (both inpatient and community) have their smoking status identified and recorded in health care records.…”
Section: Discussionmentioning
confidence: 99%
“…In the Smoking Toolkit Study, they were also associated with increased success rates for smokers with and without mental health problems (40). Additionally, smaller studies in smokers with severe mental illness who were not interested in quitting found that substantial proportions reduced their smoking by at least 50% when supplied with e-cigarettes (42,43). Clinicians should ensure that patients (both inpatient and community) have their smoking status identi ed and recorded in health care records.…”
Section: Discussionmentioning
confidence: 99%
“…In quit attempts and accompanied by behavioural support, e-cigarettes have been shown to be more effective than NRT (40). Additionally, smaller studies in smokers with severe mental illness who were not interested in quitting found that substantial proportions reduced their smoking by at least 50% when supplied with e-cigarettes (41,42). Clinicians should ensure that patients (both inpatient and community) have their smoking status identi ed and recorded in health care records.…”
Section: Discussionmentioning
confidence: 99%